Elizabeth Cady Stanton : the right is ours - Sigerman, Harriet (New York : Oxford University Press, 2001)
A biography of one of the first leaders of the women's rights movement, whose work led to women's right to vote
Includes bibliographical references (p. 135-137) and index
Keywords: Stanton, Elizabeth Cady, -- 1815-1902 -- Juvenile literature; Stanton, Elizabeth Cady, -- 1815-1902; Feminists -- United States -- Juvenile literature; Women's rights -- United States -- History -- Juvenile literature; Suffragists; Women's rights; Women -- Suffrage; Women -- Biography